Inhibition of the myotoxic activity of Bothrops asper myotoxin II in mice by immunization with its synthetic 13-mer peptide 115–129 - Calderón Fuentes, Leonel (1999)
The region comprising amino acid residues 115±129 of myotoxin II, a Lys49 phospholipase A2 from the venom of Bothrops asper, was previously shown to constitute a heparin binding site, and to be associated with its toxic activities. The corresponding synthetic peptide, KKYRYYLKPLCKK, was coupled to diphtheria toxoid as a carrier, and utilized as an immunogen in mice, to explore the possible protection from the myotoxic activity induced by myotoxin II in vivo. Mice receiving peptide-carrier injections produced antibodies to peptide 115±129, which cross-reacted to myotoxin II, as determined by enzyme-immunoassay. In contrast, no antibodies against peptide 115±129 were detected in mice immunized with myotoxin II, despite the strong antibody response to the whole antigen. Thus, region 115±129 of myotoxin II is not an immunodominant B-cell epitope in the mouse. After immunization with conjugated peptide or myotoxin II, mice were challenged with myotoxin II, and the extent of myonecrosis was estimated by determining their plasma creatine kinase activity, in comparison to non-immunized mice. After the challenge, both the group immunized with myotoxin II, and the group immunized with peptide 115±129, had a signi®cant reduction of myonecrosis. These results demonstrate that region 115±129 of myotoxin II constitutes a neutralizing epitope, and provide further evidence for the relevance of this region in its myotoxic e ect in vivo